Control over Drug Acquisition, Preparation, and Injection: Implications for HIV and HCV Risk among Young Female Injection Drug Users. (3rd June 2013) - Wagner, Karla D.; Jackson Bloom, Jennifer; Hathazi, Susan Dodi; Sanders, Bill; Lankenau, Stephen E.
Abstract : Young female injection drug users (IDUs) are at risk for HIV/HCV, and initiating the use of a new drug may confer additional and unexpected risks. While gender differences in the social context of injection drug use have been identified, it is unknown whether those differences persist during the initiation of a new drug. This mixed-methods study examined the accounts of 30 young female IDUs in Los Angeles, CA, USA from 2004 to 2006, who described the social context of initiating injection drug use and initiating ketamine injection. The analysis aimed to understand how the social context of young women's injection events contributes to HIV/HCV risk. Women's initiation into ketamine injection occurred approximately 2 years after their first injection of any drug. Over that time, women experienced changes in some aspects of the social context of drug injection, including the size and composition of the using group. A significant proportion of women described injection events characterized by a lack of control over the acquisition, preparation, and injection of drugs, as well as reliance on friends and sexual partners. Findings suggest that lack of control over drug acquisition, preparation, and injection may elevate women's risk; these phenomena should be considered as a behavioral risk factor when designing interventions.